Foreign languages in advertising: Theoretical implications for language-related IB research - Jos Hornikx; Frank van Meurs; Helene Tenzer (Journal of International Business Studies, 2023)
Given the multilingual nature of global business, language influences international business (IB) in almost all areas. IB scholars have studied the complex influence of language with manifold theoretical lenses, but have not systematically integrated linguistic theories. Aiming to broaden IB's theoretical repertoire, we draw on a field that has integrated a rich array of linguistic theories with business perspectives: research on foreign languages in advertising. We review the theories linguists and advertising scholars have applied to their joint topic and apply content analysis to organize them in three theory clusters: 'language as a symbol', 'language in the mind', and 'language as means of accommodation'. These theoretical lenses provide novel insights into the meanings and mechanisms of language, which open new avenues to scrutinize the role of language in IB. For example, theories on language as a symbol may add new perspectives to research on foreignness in IB or to emerging markets research. Theories on language in the mind can explain hurdles to the strategic use of language in foreign locations and support a more sophisticated view of translation in IB. Theories on language as a means of accommodation can advance research on cross-border legitimacy and on countercultural practices in IB.
Keywords: 330; language; linguistics; advertising; marketing; communication